2014
DOI: 10.1007/s00005-014-0281-2
|View full text |Cite
|
Sign up to set email alerts
|

The MEK1/2–ERK1/2 Pathway is Activated in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a common disease that has a considerable impact on the quality of life. Alterations in signalling pathways may contribute to the ongoing inflammation and proliferation in CRSwNP. The MEK1/2-ERK1/2 pathway transmits signals from many extracellular molecules to regulate cellular processes. We examined tissue samples from nasal polyps and the inferior turbinate of patients with CRSwNP and the inferior turbinate from subjects with healthy mucosa. The expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…If this hypothesis is correct, one would expect to observe EGFR-related transcription factors to be activated in CRS tissue. Accordingly, Linke and colleagues (48) reported that the ERK1/2 pathway was activated in tissue from patients with CRSwNP. Based on the present findings, EREG is the most likely stimulus of this activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…If this hypothesis is correct, one would expect to observe EGFR-related transcription factors to be activated in CRS tissue. Accordingly, Linke and colleagues (48) reported that the ERK1/2 pathway was activated in tissue from patients with CRSwNP. Based on the present findings, EREG is the most likely stimulus of this activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that interleukin (IL)-1β regulates the expression of glucocorticoid receptor isoforms in nasal polyps in vitro via p38 MAPK and JNK signal transduction pathways, supporting the role of MAPK in the development of nasal polyps [ 25 ]. Another study has shown that overexpression of the ERK/MAPK pathway is closely related to the occurrence and development of nasal polyps [ 9 ]. The findings of the present study showed that the levels of p-ERK and p-MEK in nasal polyp tissue-derived cells were elevated, indicating activation od the ERK/MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular signal-regulated kinase (ERK) and mitogen-activated protein kinase (MAPK) signaling pathway can activate a variety of nuclear transcription factors and participate in multiple intracellular protein kinase reactions to regulate the transcription and expression of related target genes, which affect cell biology, proliferation, apoptosis, inflammatory response, and other biological processes [ 7 , 8 ]. It has been shown that the expression or functional activity of key proteins in the ERK/MAPK pathway were increased in nasal polyps, suggesting that overexpression of components of the ERK/MAPK signaling pathway has a role in the pathogenesis of nasal polyps [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MEK1/2-ERK1/2 pathway is activated in CRSwNP [43]. There was an induction of the amount of MEK1/2 and phosphorylation of MEK1/2 and ERK1/2 in nasal polyps compared to healthy nasal mucosa.…”
Section: Mek1/2-erk1/2 Signaling Pathways Are Involved In Crswnpmentioning
confidence: 91%